2020
DOI: 10.3390/bs10090132
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Language Learning as a Potential Tool against Cognitive Impairment in Late-Life Depression: Two Meta-Analyses and Suggestions for Future Research

Abstract: Late-life depression (LLD) affects about an eighth of community-dwelling seniors. LLD impacts well-being, with loneliness and small social networks being typical. It has also been linked to cognitive dysfunction and an increased risk of developing dementia. Safety and efficacy of pharmacological treatments for LLD have been debated, and cognitive dysfunction often persists even after remission. Various cognitive interventions have been proposed for LLD. Among these, one has received special attention: foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 164 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…It also improves emotional well-being by increasing self-confidence and encouraging a positive attitude. Previous research similarly found out that learning English among the third-age learners brought socio-cognitive benefits to their lives (Pfenninger & Polz, 2018), promoted mental health (Brouwer et al, 2020;Nijmeijer et al, 2021;Grossmann et al, 2021), developed linguistic skills (Słowik-Krogulec, 2020), self-actualization (Lee, 2020;Klimova, 2020), general well-being and quality of life (Kramkowska et al, 2019;Pikhart & Klimova, 2020), and positive effects on the brain (Gabryś-Barker, 2020; Nilsson et al, 2021;Rivera et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It also improves emotional well-being by increasing self-confidence and encouraging a positive attitude. Previous research similarly found out that learning English among the third-age learners brought socio-cognitive benefits to their lives (Pfenninger & Polz, 2018), promoted mental health (Brouwer et al, 2020;Nijmeijer et al, 2021;Grossmann et al, 2021), developed linguistic skills (Słowik-Krogulec, 2020), self-actualization (Lee, 2020;Klimova, 2020), general well-being and quality of life (Kramkowska et al, 2019;Pikhart & Klimova, 2020), and positive effects on the brain (Gabryś-Barker, 2020; Nilsson et al, 2021;Rivera et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…The participants find it challenging to remember vocabulary and form grammatically accurate sentences as they age. Although Brouwer et al (2020) stated in their study that lifelong bilingualism can train cognitive flexibility, perhaps it would be an interesting subject of future investigation to study how to develop cognitive flexibility among third-age learners.…”
Section: Discussionmentioning
confidence: 99%
“…This is underscored by studies that have shown language training to be most ( cognitively) effective for those older adults with lower baseline working memory ( Kliesch et al, 2022). Age-associated mood disorders are typically taken to comprise older adults with (a history of) depression ( Brouwer et al, 2020). While treatments are generally successful in reducing depressive symptoms, the often co-occurring cognitive impairment typically persists ( Bhalla et al, 2006).…”
Section: Language Teaching Methodsmentioning
confidence: 99%
“…The effects of language learning on subjective well-being have been largely ignored until now, even though language learning is an inherently social activity (Brouwer et al, 2020). Recent qualitative work has found gains in (linguistic) self-confidence and subjective well-being due to language learning Pfenninger & Polz, 2018;Valis et al, 2019).…”
Section: Well-being Outcomesmentioning
confidence: 99%
See 1 more Smart Citation